A pilot comparative study of one-way versus two-way text message program to promote physical activity among people with severe mental illness. (October 2017) - Chen, Ming-De; Chang, Jyh-Jong; Kuo, Chang-Chih; Yu, June-Wei; Huang, Mei-Feng; Marks, Beth; Chang, Yen-Ching
Abstract: Background: Low participation in physical activities may contribute to the physical health disparity that has been found between people with severe mental illness (SMI) and the general population. Aims: This study examined the feasibility of a telehealth promotion system in people with SMI and compared the daily step counts and health outcomes between those who received one-way versus two-way text messages. Method: A pilot single-blinded comparative study was used. Participants were randomly assigned to a one-way text message group (n = 8) or a two-way text message group (n = 7). The intervention for both groups lasted for 12 weeks. All participants were asked to wear a digital pedometer every day. Results: During the 12-week intervention, the one-way and two-way text message groups increased their number of daily steps by 331.9 ± 1382.6 and 1245.4 ± 1681.1, on average, respectively. The two-way text message group showed significant improvement in the number of daily steps as compared to the baseline in weeks 6 and 11 (increases of 21% and 32%, respectively, p < 0.05). No significant differences were found between groups or within the one-way text message group. Conclusions: The feasibility of the telehealth promotion system was demonstrated among people with SMI and may increase daily step counts. People with SMI may improve their physical activity levels with two-way messaging. Future research should address the small sample limitation and better investigate the efficacy of different characteristics of mobile text messaging. Highlights: Promoting increased physical activity via text messaging is feasible and acceptable among people with SMI. Mental health staff may consider using two-way text message to improve the physical activity levels of people with SMI. The digital pedometer with a downloadable data feature made it possible to understand step changes during the intervention.